ความพึงพอใจและความต้องการของผู้รับบริการต่อบริการปฐมภูมิ ของสถานีอนามัยและศูนย์บริการสาธารณสุขเทศบาล จังหวัดปราจีนบุรี - จอมใจ พิณสาย (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study consumers satisfaction and expectation to primary care of health center in Prachin Buri province in terms of management, service, and technical. Research design: Cross-sectional descriptive study. Study population: Consumers taking service at Primary Care Unit in health center of 2 urban areas and 6 suburb areas in Prachin Buri Province. Sample size: Five hundreds and forty two samples were randomly selected by multistage sampling. Research tool: Self-administered and interview questionnaire. Data collection: The study was conducted between January 1, 2003 to February 28, 2003. Statistical method: Unpaired t-test, Paired t-test and One-way ANOVA. Results: The total respondents were 195 urban clients (36.0%) and 347 suburban clients (64.0%). The majority of them were married (72.9%), primary education (68.2%), taking employment (38.9%), had ever been referred through the network hospital (19.9%): 40.7% and 36.1% highly satisfied with co-ordination between hospital and health center and follow-up care respectively. There were 30 out of 32 activities specified in 3 dimensions obtained high satisfaction scores (score 4 and 5), therefore, all activities mentioned were rated as high future expectation by more than half of the client respondents. Furthermore, 20 out of 32 activities were scored high satisfaction by the urban clients in contrast with highly satisfied scores in all activities listed by the suburban clients. The least satisfaction was identified as adequate essential drugs. In comparison between satisfaction and expectation, 28 out of 32 activities were found statistically significant different (p<0.001) particularly adequacy/readiness of equipments and diagnostic tools. Regarding sex, occupation, level of income, health status, service unit preferred, travel time, services time, information disclosed, setting and rights were shown statistically significant different (p<0.05). Finally, 87.5% of clients stated as better services than before and they will reselect. However, doctors hours and more equipments were called for. Conclusion: This study revealed many critical success factors influencing the clients satisfaction. Continuous services quality improvement were needed to fill the gaps identified especially adequate of doctor hours and equipments, and more effective referral system for nurturing health development of the local people